Kritik Terjemah Novel Bercinta di Antara Ruang Sakral dan Profan Karya Taufiq El- Hakim - Tika Fitriyah (Madah: Jurnal Bahasa dan Sastra, 2024)
This research is a qualitative descriptive study with a source of data being the novel "Usfur min asy-Syarq" with its translation titled "Bercinta di antara Ruang Sakral dan Profan". This research uses a translation critique approach proposed by Newmark. The research method in this study uses the free sima method with a purposive sampling technique. The results of this study show that the translation of this novel has many advantages in terms of readability, as the translator presents the story of the novel with beautiful and easily understood language. The translation technique most often used in this research is discursive creation. However, in terms of accuracy, this translation has many shortcomings, this is due to the translator removing many parts of the source language so that it is not translated, and also because the translator frequently shifts the meaning, this is due to the translator translating words and phrases that are too far from their original meaning in the source language.